Chapter Employability-Oriented Curriculum: Strategies and Tools to Train Young Graduates. The PRIN EMP&Co. Project - GIOLI, GAIA (Studies on Adult Learning and Education, 2018)
This paper focuses on the impact of employability-oriented modules on the design, planning, and implementation of work transitions. It takes its lead from the PRIN EMP&Co project developed by the University of Florence in 2014-2017, and how its research protocol allows a mapping of the construction of employability during the Master's Degree Course